Intervención para el mejoramiento de la capacidad de resiliencia de los funcionarios de la Unidad de Atención de Peritaje Integral de la Unidad de Flagrancia del Distrito Metropolitano de Quito - Manguia Durán, Deysi Anabel (2017)
The purpose of this degree paper is to present the systematization of the project: "Intervention for the improvement of the Resilience capacity of the officials of the Attention Unit of Integral Expertise of the Unit of Flagrance of the Metropolitan District of Quito." The results of the application of the project for the improvement of the resilience capacity, as well as the role of self-care and catharsis and containment spaces, are shown in these results. Therefore, the axis of systematization that will guide the organization and interpretation of information, is resilience. For the reconstruction of the intervention experience, tools of quantitative and qualitative order were used. On the one hand, the construction of an entrance and exit questionnaire that allowed to measure the effect of the intervention on the self-care practices, through a statistical description of the changes observed before and after the intervention. On the other hand, unstructured interviews were carried out to collect information on the resilient pillars of the staff, as well as the impact of their work on a personal level; The qualitative information obtained was organized through emptying matrices and was interpreted through categorial analysis. It was concluded from the description of quantitative results as well as from the interpretation of qualitative information that self-care positively affects the resilience capacity and is enhanced by catharsis and containment space.